Pengembangan Pendidikan melalui Sekolah Bertaraf Internasional - Lestari, Inda; Habibah, Aulia; Khoiriyah, Alfi; Indriyani, Fauziyah (Lembaga Yasin AlSys, 2022)
The Indonesian government, that intiated the legislation of the treaty system was a prelude to its annual efforts to promote schools to meet the international standardsof school (SBI),the 2003 school teaching system (SBI) specifically the stature no 20,Report that “government and/or abupatent increases the one school minimum ata rate to be promoted at school with inferior international (SBI) set up SBI could only give birth to the students who is capable of advanced intelligence and more exclusive education servicesas if by the wealthy or the wealthy,and a great deal of commercial education. In this study,reserchers have attempted to describe a school of Internatiobal educatiaon.as it relates to understanding,managemen of characteristics and how developming a multi world school,with students parents showing stidents keen interest in education and more.